MicroRNA‐7 negatively regulates Toll‐like receptor 4 signaling pathway through FAM177A. Issue 1 (19th October 2020) - Chen, Huizi; Guo, Mengmeng; Yue, Dongxu; Zhao, Juanjuan; Zhou, Ya; Chen, Chao; Liang, Guiyou; Xu, Lin
Summary: Toll‐like receptor (TLR) 4 signalling is critical for innate immunoinflammatory response and widely triggers the development of various types of clinical diseases. MicroRNA‐7 (miR‐7) is well documented to play an important regulatory role in various biological events. However, the exact role of miR‐7 in TLR4 signalling pathway remains to be fully elucidated. In the present study, we found that miR‐7 expression in TLR4 signalling‐activated bone marrow‐derived macrophages (BMDMs) stimulated by LPS was dramatically increased. Importantly, miR‐7 deficiency significantly enhanced the production of related inflammatory cytokines including IL‐1β, IL‐6 and IL‐12, as well as TNF‐α, on LPS‐activated BMDMs, accompanied by elevated transduction of TLR4 signalling including Myd88‐dependent and Myd88‐independent pathways, whereas miR‐7 overexpression significantly decreased the transduction of TLR4 signalling and the production of related inflammatory cytokines. Mechanistically, we identified family with sequence similarity 177, member A (FAM177A) as a novel target molecule of miR‐7. Furthermore, down‐regulation of FAM177A using RNAi could impair the transduction of TLR4 signalling. Finally, down‐regulation of FAM177A also reversed the effect of miR‐7 deficiency on TLR4 signalling transduction and production of related inflammatory cytokines on BMDMs. Therefore, we provide the new evidence that miR‐7 acts as a novel negative fine‐tuner in regulating TLR4 signalling pathways by targeting FAM177A, which might throw light on the basal understanding on the regulatory mechanism of TLR4 signalling and benefit the development of therapeutic strategies against related clinical diseases. Abstract : In the present study, we found that miR‐7 expression in TLR4 signalling‐activated bone marrow‐derived macrophages (BMDMs) stimulated by LPS was dramatically increased. Importantly, miR‐7 deficiency significantly enhanced the production of related inflammatory cytokines including IL‐1β, IL‐6 and IL‐12, as well as TNF‐α, on LPS‐activated BMDMs, accompanied by elevated transduction of TLR4 signalling including Myd88‐dependent and Myd88‐independent pathways. Mechanistically, we identified family with sequence similarity 177, member A (FAM177A) as a novel target molecule of miR‐7.